Chironji mediated facile green synthesis of ZnO nanoparticles and their photoluminescence, photodegradative, antimicrobial and antioxidant activities. (December 2015) - Suresh, D.; Nethravathi, P.C.; Udayabhanu,; Pavan Kumar, M.A.; Raja Naika, H.; Nagabhushana, H.; Sharma, S.C.
Abstract: This study reports a facile green synthesis method of Zinc oxide nanoparticles (ZnO Nps) using aqueous extract of Chironji ( Buchanania lanzan ) leaves as fuel by solution combustion method. The ZnO Nps were characterized by XRD, TEM and UV–visible techniques. The Nps were evaluated for photoluminescence, photodegradation, antimicrobial and antioxidant activities. The extract was found to be rich in antioxidants with 26% polyphenols and 25% flavonoids. X-ray diffraction patterns of Nps were indexed to hexagonal wurtzite structure. The photoluminescence studies reveal strong red emission due to Oxygen-vacancy and Zn-vacancies. The ZnO Nps exhibit efficient photodegradation of Malachite green (MG) dye in presence of Sun light and UV light. Nps showed significant antibacterial activity on Klebsiella aerogenes, Escherichia coli, Pseudomonas desmolyticum and Staphylococcus aureus . The ZnO Nps elicit antioxidant activity by inhibiting the activity of 1, 1-Diphenyl-2-picrylhydrazyl (DPPH) free radicals. The study successfully demonstrates an environment friendly and simple method of synthesis of multifunctional ZnO Nps using antioxidant rich aqueous extract of plant material.